PENGARUH INKLUSI KEUANGAN, FINANCIAL TECHNOLOGY DAN PENGELOLAAN KEUANGAN TERHADAP KINERJA UMKM PEDESAAN DI MADURA - Rozalinda; Moh. Zaki Kurniawan (Fakultas Ekonomi Universitas Kadiri, 2023)
The reason for this study is to decide the impact of financial inclusion, financial technology, and financial management on the performance of rural MSMEs in Madura. The population of this study consists of rural MSMEs in Madura. In taking respondents, there were 100 people who were addressed to MSME entertainers by distributing questionnaires, this study utilizes the purposive sampling method in deciding the example. The study findings indicate that there is an impact of financial inclusion and financial management on MSME performance, however financial technology has no impact on the performance of MSMEs.